Evolution and developmental functions of the dystrophin-associated protein complex: beyond the idea of a muscle-specific cell adhesion complex - Mirouse, Vincent (Frontiers in Cell and Developmental Biology, 2023)
The Dystrophin-Associated Protein Complex (DAPC) is a well-defined and evolutionarily conserved complex in animals. DAPC interacts with the F-actin cytoskeleton via dystrophin, and with the extracellular matrix via the membrane protein dystroglycan. Probably for historical reasons that have linked its discovery to muscular dystrophies, DAPC function is often described as limited to muscle integrity maintenance by providing mechanical robustness, which implies strong cell-extracellular matrix adhesion properties. In this review, phylogenetic and functional data from different vertebrate and invertebrate models will be analyzed and compared to explore the molecular and cellular functions of DAPC, with a specific focus on dystrophin. These data reveals that the evolution paths of DAPC and muscle cells are not intrinsically linked and that many features of dystrophin protein domains have not been identified yet. DAPC adhesive properties also are discussed by reviewing the available evidence of common key features of adhesion complexes, such as complex clustering, force transmission, mechanosensitivity and mechanotransduction. Finally, the review highlights DAPC developmental roles in tissue morphogenesis and basement membrane (BM) assembly that may indicate adhesion-independent functions.